2021
DOI: 10.3389/fonc.2021.774117
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis of Contrast-Enhanced CT for the Preoperative Prediction of Microvascular Invasion in Mass-Forming Intrahepatic Cholangiocarcinoma

Abstract: BackgroundMicrovascular invasion (MVI) has been shown to be closely associated with postoperative recurrence and metastasis in patients with intrahepatic cholangiocarcinoma (ICC). We aimed to develop a radiomics prediction model based on contrast-enhanced CT (CECT) to distinguish MVI in patients with mass-forming ICC.Methods157 patients were included and randomly divided into training (n=110) and test (n=47) datasets. Radiomic signatures were built based on the recursive feature elimination support vector mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…To date, in several studies have been assessed the role of radiomics or radiogenomics in ICC [ 72 , 79 , 180 204 ]. The area of main interest has been the evaluation of recurrence after surgical resection [ 72 , 79 , 180 187 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, in several studies have been assessed the role of radiomics or radiogenomics in ICC [ 72 , 79 , 180 204 ]. The area of main interest has been the evaluation of recurrence after surgical resection [ 72 , 79 , 180 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, in several studies have been assessed the role of radiomics or radiogenomics in ICC [ 72 , 79 , 180 204 ]. The area of main interest has been the evaluation of recurrence after surgical resection [ 72 , 79 , 180 187 ]. Chu et al [ 79 ] evaluated 203 ICCs, that were allocated with a ratio of 7:3 into the training cohort and the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, despite univariate logistic regression analysis showed that tumor morphology was a signi cant clinical feature, it was not an independent feature in MVI status strati cation and overall survival prediction preoperatively. However, one con icting study reported that irregular morphology may be associated with MVI status (25), this may owe to tumor morphology is a subjective variable, and more importantly, we considered lobulated and irregular as two morphological categories, while considered as one category in his/her study. Thirdly, as in previous study (17), tumor size and intrahepatic duct dilatation were independent predictors in MVI strati cation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the presence of MVI is confirmed on histology, which is invasive. A few studies based on radiomic analysis to predict the MVI in mass‐forming ICC were reported (see, eg Reference 8). However, this approach requires accurate tumor segmentation that may not always be possible.…”
mentioning
confidence: 99%